Method for improving near-surface intergranular corrosion resistance of GH4169 alloy
By clamping the plasma generator and compressed air tube by robotic hand, the GH4169 alloy was subjected to "fast near-surface solid solution-aging integration" treatment and cooling treatment, which solved the problem of intergranular corrosion in marine corrosion environments, significantly improved the corrosion resistance of the near-surface and maintained the internal mechanical properties.
Patent Information
- Application Number
- CN202510027657.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
GH4169 alloy is prone to intergranular corrosion in marine corrosion environments, resulting in a decline in mechanical properties. The existing coating preparation technology has problems such as complex processes, expensive equipment and poor coating stability.
The plasma generator and compressed air tube are clamped by a robot, and the "fast solution-aging integrated near-surface" treatment is carried out through a high-energy plasma beam, and combined with cooling treatment, the resistance to intergranular corrosion of the near-surface GH4169 alloy is improved.
It significantly improves the intergranular corrosion resistance of the near surface of GH4169 alloy, meets the requirements of improving environmental corrosion resistance, and maintains the comprehensive mechanical properties inside the alloy.
Smart Images

Figure CN119824349A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of near-surface modification and corrosion resistance optimization of high-temperature alloys, and particularly relates to a method for improving the near-surface intergranular corrosion resistance of a GH4169 alloy. Background Art
[0002] GH4169 alloy is a face-centered cubic A1 structure Ni-Cr-Fe based high temperature alloy. The γ" phase and γ′ phase generated in the crystal after precipitation hardening give it good mechanical properties. Among them, the γ" phase is mainly body-centered tetragonal DO 22 Ni 3 Nb, this phase is a metastable strengthening phase, coherent with the matrix, strengthening the alloy in a coherent distortion manner, and is the main strengthening phase; the γ′ phase is mainly face-centered cubic LI 2 Ni3 (Al, Ti, Nb) of the structure is also coherent with the matrix, but the interface energy between the γ′ phase and the γ matrix is low, with higher organizational stability, playing an auxiliary strengthening role. In addition, the grain boundaries of the alloy are usually distributed with orthogonal DO a Ni 3 Nb (δ phase, produced during cooling or by γ" phase transformation), δ phase is not coherent with the GH4169 alloy matrix and has no strengthening effect, but δ phase with reasonable size, quantity and morphology can improve the impact toughness (reduce notch sensitivity), grain size and plasticity of the alloy.
[0003] Therefore, GH4169 alloy has good comprehensive properties in the temperature range of -253~650℃. The yield strength of this alloy below 650℃ ranks first among deformed high-temperature alloys, and it has good fatigue resistance, radiation resistance, oxidation resistance and corrosion resistance. At present, GH4169 alloy has been widely used in the field of marine engineering that requires high temperature, high pressure, high load and long life.
[0004] GH4169 alloy has good seawater corrosion resistance, mainly because the surface of the nickel-based alloy will produce a dense oxide film in the electrolyte or humid air, which separates the matrix from the corrosive environment to protect the matrix alloy from further corrosion. However, this passive film has poor durability and cannot completely protect the matrix. It will not only be destroyed by tribological contact, but also by some corrosive ions (such as Cl — ,Br — ) breakdown and cause local pitting. In order to ensure the good plasticity and impact toughness of GH4169 alloy, a certain amount of δ phase that is incoherent with the austenite matrix is usually distributed at the grain boundary of the alloy. aThe δ phase of the structure is incoherent with the matrix phase of the face-centered cubic A1 structure and has a large difference in crystal structure, which leads to a disordered atomic arrangement at the grain boundaries of the GH4169 alloy and high chemical activity. Under the same external corrosive medium conditions, the grain boundaries of the alloy are prone to selective intergranular corrosion, which will significantly destroy the bonding force between the grains and greatly reduce the mechanical properties of the alloy. This poses a great challenge to the durability and safety of the GH4169 alloy in marine corrosion environments.
[0005] At present, the addition of corrosion-resistant coating is one of the important methods to improve the corrosion resistance of GH4169 alloy. The existing coating preparation technologies mainly include thermal spraying technology, chemical vapor deposition technology (CVD), physical vapor deposition technology (PVD), etc. Thermal spraying technology sprays the material in the form of powder or wire onto the surface of the substrate to form a coating, but the thickness of the coating prepared is uneven and the surface is relatively rough, and the bonding strength between the coating and the substrate is low, which affects the stability and durability of the coating. CVD is a surface technology that uses volatile compounds or single vapors containing various elements in the film layer to produce a gas-phase chemical reaction on the surface of the hot substrate, and the reaction products form a deposited coating; PVD is a method of heating a solid material to a high temperature, evaporating it into a gas, and then depositing the gas onto the surface of the substrate to form a thin film. However, both CVD technology and PVD technology face the problems of complex process, expensive equipment, and can only be used for the deposition of specific materials, and there are many limitations in practical application. Summary of the invention
[0006] In order to solve the above problems, the object of the present invention is to provide a method for improving the near-surface intergranular corrosion resistance of GH4169 alloy.
[0007] In order to achieve the above object, the method for improving the near-surface intergranular corrosion resistance of GH4169 alloy provided by the present invention comprises the following steps performed in sequence:
[0008] 1) Clamp GH4169 alloy as a specimen, and use programming to design the moving path and moving speed of the manipulator on the specimen surface;
[0009] 2) The plasma generator is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed, and the surface of the sample is subjected to multiple "near-surface rapid solid solution-aging integration" treatments by the high-energy plasma beam generated by the plasma generator;
[0010] 3) A dry and clean compressed air pipe is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed, and the surface of the sample is cooled multiple times by compressed air from the compressed air pipe to obtain a GH4169 alloy having anti-intergranular corrosion performance near the surface.
[0011] In step 1), the moving speed of the robot is 990-1010 mm / s, and the distance between two adjacent rows in the moving path is 8-10 mm.
[0012] In step 2), the distance between the plasma generator and the sample is 68-72 mm, the power is 22.8-23.2 KW, the high-energy plasma beam treats the sample surface 3-5 times, and the time interval between two adjacent times is 8-10 s.
[0013] In step 3), the pressure of the compressed air is 0.2-0.3 MPa, and the number of cooling treatments is 8-10 times.
[0014] The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy provided by the present invention has the following advantages:
[0015] (1) The process is simple and efficient. The entire process only requires three steps. No additional pre-treatment and post-treatment are required, and no other functional materials or subtractive processing is required. The near-surface intergranular corrosion resistance of GH4169 alloy can be significantly improved through the "near-surface rapid solid solution-aging integration" treatment technology of high-energy plasma beam.
[0016] (2) By using the "near-surface rapid solid solution-aging integration" treatment technology, rapid solid solution and aging treatment can be carried out at a depth of about 40μm from the surface of the GH4169 alloy, achieving the near-surface intergranular corrosion resistance of the GH4169 alloy, and the corrosion performance near the surface is improved by more than 1 times compared with the interior of the alloy. On the one hand, it meets the requirements for improving the environmental corrosion resistance of the GH4169 alloy; on the other hand, since the microstructure inside the GH4169 alloy is not changed, the comprehensive mechanical properties of the GH4169 alloy are guaranteed not to decrease.
[0017] (3) By precisely controlling various parameters in the process of “near-surface rapid solution-aging integration”, including the distance between the plasma generator and the sample, the movement rate of the manipulator, the time interval between two adjacent times, and the number of cooling treatments, it can be ensured that the near-surface grains of the GH4169 alloy do not grow significantly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The invention provides a cross-sectional low-magnification microstructure of a GH4169 alloy having near-surface intergranular corrosion resistance.
[0019] Figure 2 The high-magnification microstructure of the cross section of the GH4169 alloy with near-surface intergranular corrosion resistance provided by the present invention, wherein Figure (a) shows the near-surface intergranular corrosion resistant layer microstructure at a depth of about 40 μm from the surface of the GH4169 alloy, Figure (b) shows the internal microstructure of the GH4169 alloy at a depth of about 40 to 80 μm from the surface of the GH4169 alloy, and Figure (c) shows the internal microstructure of the GH4169 alloy at a depth of about 80 to 140 μm from the surface of the GH4169 alloy.
[0020] Figure 3 The cross-sectional low-power microstructure of the GH4169 alloy with near-surface intergranular corrosion resistance provided by the present invention after being corroded for different times in a corrosion reagent consisting of 2g of cupric chloride + 40ml of hydrochloric acid + 40ml of alcohol, wherein the corrosion time in Figure (a) is 60s, and the corrosion time in Figure (b) is 120s. DETAILED DESCRIPTION
[0021] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0022] Embodiment 1:
[0023] The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy provided in this embodiment comprises the following steps performed in sequence:
[0024] 1) Clamp GH4169 alloy as a sample, and use programming to design the moving path and moving speed of the manipulator on the sample surface; the moving speed of the manipulator is 990 mm / s, and the distance between two adjacent rows in the moving path is 8 mm;
[0025] 2) The plasma generator is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed. The surface of the sample is subjected to three "near-surface rapid solid solution-aging integration" treatments by the high-energy plasma beam generated by the plasma generator. The distance between the plasma generator and the sample is 68 mm, the power is 22.8 KW, and the time interval between two adjacent times is 8 s;
[0026] 3) A dry and clean compressed air pipe is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed. The surface of the sample is cooled 8 times by compressed air from the compressed air pipe. The pressure of the compressed air is 0.2 MPa, and a GH4169 alloy having anti-intergranular corrosion performance near the surface is obtained.
[0027] Embodiment 2:
[0028] The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy provided in this embodiment comprises the following steps performed in sequence:
[0029] 1) Clamp GH4169 alloy as a sample, and design the moving path and moving speed of the manipulator on the sample surface by programming; the moving speed of the manipulator is 1000 mm / s, and the distance between two adjacent rows in the moving path is 9 mm;
[0030] 2) The plasma generator is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed. The surface of the sample is subjected to four "near-surface rapid solid solution-aging integration" treatments by the high-energy plasma beam generated by the plasma generator. The distance between the plasma generator and the sample is 70 mm, the power is 23 KW, and the time interval between two adjacent times is 9 s;
[0031] 3) A dry and clean compressed air pipe is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed. The surface of the sample is cooled 9 times by compressed air from the compressed air pipe. The pressure of the compressed air is 0.25 MPa, and a GH4169 alloy having anti-intergranular corrosion performance near the surface is obtained.
[0032] Embodiment 3:
[0033] The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy provided in this embodiment comprises the following steps performed in sequence:
[0034] 1) Clamp GH4169 alloy as a sample, and use programming to design the moving path and moving speed of the manipulator on the sample surface; the moving speed of the manipulator is 1010 mm / s, and the distance between two adjacent rows in the moving path is 10 mm;
[0035] 2) The plasma generator is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed, and the surface of the sample is subjected to four "near-surface rapid solid solution-aging integration" treatments by the high-energy plasma beam generated by the plasma generator. The distance between the plasma generator and the sample is 72 mm, the power is 23.2 KW, and the time interval between two adjacent times is 10 s;
[0036] 3) A dry and clean compressed air pipe is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed. The surface of the sample is cooled 10 times by compressed air from the compressed air pipe. The pressure of the compressed air is 0.3 MPa, and a GH4169 alloy having anti-intergranular corrosion performance near the surface is obtained.
[0037] Figure 1The cross-sectional low-power microstructure of the GH4169 alloy with near-surface intergranular corrosion resistance provided by the present invention. Figure 1 Analysis shows that after the "near-surface rapid solid solution-aging integration" treatment, the near-surface microstructure of the GH4169 alloy (hereinafter referred to as the near-surface treatment zone) has changed, and both the grain boundary and the interior of the grain are significantly different from the interior of the alloy. There is a continuous transition between the near-surface treatment zone and the interior of the GH4169 alloy without any interface, and the thickness of the near-surface treatment zone is about 40μm.
[0038] Figure 2 The high-magnification microstructure of the cross section of the GH4169 alloy with near-surface intergranular corrosion resistance provided by the present invention, wherein Figure (a) shows the near-surface intergranular corrosion resistant layer microstructure at a depth of about 40 μm from the alloy surface, Figure (b) shows the internal microstructure of the GH4169 alloy at a depth of about 40 to 80 μm from the alloy surface, and Figure (c) shows the internal microstructure of the GH4169 alloy at a depth of about 80 to 140 μm from the alloy surface. From the analysis of Figure (a), it can be seen that there is no obvious grain boundary in the near-surface treatment area, the δ phase content is very low (small number, small scale), while a large number of strengthening phases are dispersed inside the grains; from the analysis of Figure (b), it can be seen that there are more δ phases distributed at the internal grain boundaries of the GH4169 alloy at a depth of about 40 to 80 μm from the alloy surface, and there are few strengthening phases distributed inside the crystal; from the analysis of Figure (c), as the distance increases to 80 to 140 μm, the δ phase content distributed at the internal grain boundaries of the GH4169 alloy increases, and there is almost no strengthening phase inside the crystal. In summary, first, after the "near-surface rapid solid solution-aging integration" treatment, the near-surface treatment area of the GH4169 alloy has undergone a rapid solid solution process of the δ phase at the grain boundary and a rapid precipitation process of the strengthening phase inside the crystal. The solid solution of the δ phase at the grain boundary in the near-surface treatment area has greatly reduced the degree of disorder of the atomic arrangement at the grain boundary, thereby improving the intergranular corrosion resistance of the GH4169 alloy near the surface. Second, the precipitation of the dispersed strengthening phase inside the crystals in the near-surface treatment area is beneficial to improving the hardness and strength of the near-surface area of the GH4169 alloy. Third, the internal microstructure of the GH4169 alloy above 40μm from the surface has not changed, maintaining the original comprehensive mechanical properties of the GH4169 alloy.
[0039] Figure 3The cross-sectional low-power microstructure of the GH4169 alloy with near-surface intergranular corrosion resistance provided by the present invention after being corroded for different times in a corrosive agent (2g copper chloride + 40ml hydrochloric acid + 40ml alcohol), wherein the corrosion time of Figure (a) is 60s, and the corrosion time of Figure (b) is 120s. As shown in Figure (a), after 60s of immersion corrosion, almost no corrosion occurs at the grain boundaries of the near-surface treatment area, while obvious corrosion has occurred at the grain boundaries inside the GH4169 alloy; as shown in Figure (b), after 120s of immersion corrosion, slight corrosion occurs at the grain boundaries of the near-surface treatment area, and the grain size of the near-surface treatment area has not increased significantly, while serious corrosion has occurred at the grain boundaries inside the GH4169 alloy as the corrosion time increases.
Claims
1. A method for improving the near-surface intergranular corrosion resistance of GH4169 alloy, characterized in that: The method for improving the near-surface intergranular corrosion resistance of the GH4169 alloy comprises the following steps performed in sequence: 1) Clamp GH4169 alloy as a specimen, and use programming to design the moving path and moving speed of the manipulator on the specimen surface; 2) The plasma generator is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed, and the surface of the sample is subjected to multiple "near-surface rapid solid solution-aging integration" treatments by the high-energy plasma beam generated by the plasma generator; 3) A dry and clean compressed air pipe is clamped by a manipulator, and the manipulator is moved along the above-mentioned moving path at the above-mentioned moving speed, and the surface of the sample is cooled multiple times by compressed air from the compressed air pipe to obtain a GH4169 alloy having anti-intergranular corrosion performance near the surface.
2. The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy according to claim 1, characterized in that: In step 1), the moving speed of the robot is 990-1010 mm / s, and the distance between two adjacent rows in the moving path is 8-10 mm.
3. The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy according to claim 1, characterized in that: In step 2), the distance between the plasma generator and the sample is 68-72 mm, the power is 22.8-23.2 KW, the high-energy plasma beam treats the sample surface 3-5 times, and the time interval between two adjacent times is 8-10 s.
4. The method for improving the near-surface intergranular corrosion resistance of GH4169 alloy according to claim 1, characterized in that: In step 3), the pressure of the compressed air is 0.2-0.3 MPa, and the number of cooling treatments is 8-10 times.